Drug Interaction of Glycyrrhiza glabra L. with Chemical Drugs: A mini Review Article - Pegah Shahkib; Mahmoud Bahmani; Pouya Parsaee (Plant Biotechnology Persa, 2020)
Glycyrrhiza glabra L. is a valuable medicinal and nutritional plant of the Fabaceae family. In traditional medicine, it is used to treat duodenal ulcers, coughs, sore throats, inflammation, bloating, strong laxatives and antidotes, hot flashes, relieves thirst, relieves skin discomfort, and anti-allergies. The most important active ingredient in this plant is glycyrrhizic acid. G. glabra L. is a widely used plant in Iran and medicinal products have been produced from it in Iran. Interactions between herbal and chemical drugs are also common. In this review study, drug interactions between G. glabra L. and chemical corticosteroid drugs were investigated and reported. G. glabra L.  can interact with a variety of chemical drugs, so concomitant use of G. glabra L. with other drugs requires caution.